Anesthetic considerations for endovascular treatment in stroke therapy. Issue 4 (5th August 2022) - Stolp, Jeffrey; Coutinho, Jonathan M.; Immink, Rogier V.; Preckel, Benedikt
Abstract : Purpose of review: The introduction of clot removement by endovascular treatment (EVT) in 2015 has improved the clinical outcome of patients with acute ischemic stroke (AIS) due to a large vessel occlusion (LVO). Anesthetic strategies during EVT vary widely between hospitals, with some departments employing local anesthesia (LA), others performing conscious sedation (CS) or general anesthesia (GA). The optimal anesthetic strategy remains debated. This review will describe the effects of anesthetic strategy on clinical and radiological outcomes and hemodynamic parameters in patients with AIS undergoing EVT. Recent findings: Small single-center randomized controlled trails (RCTs) found either no difference or favored GA, while large observational cohort studies favored CS or LA. RCTs using LA as separate comparator arm are still lacking and a meta-analysis of observational studies failed to show differences in functional outcome between LA vs. other anesthetic strategies. Advantages of LA were shorter door-to-groin time in patients and less intraprocedural hypotension, which are both variables that are known to impact functional outcome. Summary: The optimal anesthetic approach in patients undergoing EVT for stroke therapy is still unclear, but based on logistics and peri-procedural hemodynamics, LA may be the optimal choice. Multicenter RCTs are warranted comparing LA, CS and GS with strict blood pressure targets and use of the same anesthetic agents to minimize confounding variables.